Diagnostic markers for Teratosphaeria destructans and closely related species. Issue 6 (27th October 2020) - Havenga, Minette; Wingfield, Brenda D.; Wingfield, Michael J.; Dreyer, Léanne L.; Roets, Francois; Aylward, Janneke
Abstract: Teratosphaeria foliar pathogens cause leaf and shoot blight on Eucalyptus trees in many parts of the world. Among them, T. destructans is one of the most aggressive pathogens causing defoliation of young Eucalyptus trees in tropic regions. Identification of T. destructans to species level is currently not possible based solely on morphological characteristics or ITS sequence data. The aim of this study was to assess T. destructans microsatellites and a newly developed T. epicoccoides microsatellite as a diagnostic tool to differentiate among T. destructans and several closely related foliar pathogens. Based on the number of markers that amplified, the T. destructans microsatellites allowed for the differentiation of T. destructans, T. epicoccoides, T. eucalypti, T. nubilosa, T. pseudoeucalypti and T. viscidus . These microsatellites provide a rapid and cost‐effective diagnostic tool that will enable the identification of a large number of isolates important in disease surveys and inoculation trials.